The Prosperity Gospel: A Critique of the Way the Bible is Used - Adeleye, Femi B. (Lausanne Movement, 2015)
Introduction The ‘prosperity gospel’ which is also variously referred to as the ‘health and wealth gospel’, ‘Name it, claim it gospel’, or ‘Gospel of greed’ is one of the fastest growing emphasis within the contemporary Church. Initially prominent in Pentecostal and Charismatic Churches, it has now spread across various denominations and Church traditions. The gospel…
free